Influence of negative parental attachment styles, self-efficacy and moral competence on academic dishonesty among undergraduates in Selangor, Malaysia - Lee, Gwan Yew (2019)
Academic dishonesty is a rising trend in the current academic world, especially in tertiary education levels. Undergraduates will resort to cheating for the sake of their CGPA, to maintain their scholarship or to even secure their work opportunity upon graduation. The objective of this study was to investigate the relationship between negative parental attachment styles (anxiety and avoidant), self-efficacy, moral competence and academic dishonesty among undergraduates in Selangor, Malaysia.